New Avenues for Regional Innovation Systems - Theoretical Advances, Empirical Cases and Policy Lessons (Springer International Publishing, 2018)
This book discusses the latest theoretical advances in regional innovation research, presents empirical cases involving the development of regional innovation systems (RISs), and explores regional innovation policy approaches. Grounded in the extensive literature on RISs, it addresses state-of-the-art developments in light of recent theoretical advances in economic geography and related disciplines. Written in honor of Bjørn Asheim's seventieth birthday, the book includes novel and carefully selected chapters prepared by collaborators, colleagues and former PhD-students of one of the founding fathers of RIS research. Further, it makes a significant contribution to the academic debate on regional innovation and growth and offers valuable insights for scholars and policymakers alike.